The Influence of Business Networks and Perception of Product Quality on the Competitive Advantage of SME Products in Langkat - Hou, Amin; Deva Djohan; Widy Hastuty (YAYASAN BINA BISNIS NUSANTARA MEDAN, 2024)
This study seeks to assess the influence of business networks and perceptions of product quality on the competitive advantage of small and medium companies (SMEs) in Langkat. Small and medium-sized enterprises (SMEs) are vital for fostering local economic development; yet, company stakeholders encounter escalating competitive constraints. corporate networks are seen as a strategic asset that facilitates access to broader markets, resources, and information essential for corporate development. Simultaneously, perceptions of product quality affect consumer image and trust, which are essential for sustaining excellence in a competitive marketplace. This research employs a quantitative methodology, utilizing data gathered from a survey of SMEs in Langkat. We employ multiple linear regression analysis methods to examine the simultaneous and partial impacts of the variables under investigation. The analytical results demonstrate that business networks and perceptions of product quality substantially affect competitive advantage. The findings underscore the necessity for SMEs to broaden their business networks and enhance product quality to compete successfully. Recommendations include enhancing company collaboration and creating creative goods that fulfill consumer expectations